BAGAIMANA PERTIMBANGAN HAKIM TERHADAP KEKUATAN PEMBUKTIAN SAKSI TESTIMONIUM DE AUDITU DALAM PERKARA PENCABULAN ANAK PADA PUTUSAN NOMOR: 36/Pid.Sus/2023/PN Lbb - Ricky Febriyansyah Akbar; Zakki Adlhiyati (Sebelas Maret University, 2025)
This paper aims to analyze the evidentiary strength of testimonium de auditu (hearsay witness testimony) in a child molestation case, as addressed in Decision No. 36/Pid.Sus/2023/PN Lbb. The research method employed is normative or doctrinal legal research, which is prescriptive and applied in nature. The approach used in this study is a case study approach. The legal materials utilized consist of both primary and secondary sources. Primary legal materials include statutory regulations and court decisions, while secondary legal materials comprise books, legal journals, theses/dissertations, and online sources. The legal materials were collected through a literature study and analyzed using syllogistic deduction, based on major and minor premises. The study concludes that the hearsay witness testimonies submitted in this case were not taken into consideration by the judges, as they originated from unsworn witnesses and were inconsistent, thereby failing to establish judicial conviction.